Keteguhan Iman Sebagai Jaminan Keselamatan Dalam Surat Yudas dan Relevansinya Bagi Gereja Masa Kini - Taninas, Gaudensius; Oswin Koba, Cosmas; Manhitu, Joni; SemarTaek, Jonisius; Amalo, Piere A.; Senda, Siprianus S. (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The letter of Jude is one of seven Catholic letters in the Christian Bible. His main advice is to resist the error of false teachers. For the Church, false teachers are a doctrinal threat that distorts Christian doctrine and the life orientation of believers towards destruction. Today's church faces challenges where material things are glorified and God is no longer a guide. This research is a qualitative descriptive study with the nature of a literature review. The researchers tried to explore the content of the message of Jude's letter and how it is actualized in the context of the contemporary Church. The goal is for every person who believes in Christ to have an awareness of faith in responding to today's world. Firm faith is the way to survive various worldly temptations.